Kinematic and dynamic analysis of a serial manipulator with local closed loop mechanisms - My, Chu Anh; Hoan, Vu Minh (Vietnam Journal of Mechanics, 2019)
This paper addresses the kinematic and dynamic modelling and analysis for a robot arm consisting of two hydraulic cylinders driving two revolute joints of the arm. The two cylinders and relevant links of the robot constitute two local closed kinematic chains added to the main robot mechanism. Therefore, the number of the generalized coordinates of the mechanical system is increased, and the mathematical modelling is more complex that requires a formulation of constraint equations with respect to the local closed chains. By using the Lagrangian formulation with Lagrangian Multipliers, the dynamic equations are first derived with respect to all extended generalized coordinates. Then a compact form of the dynamic equations is yielded by canceling the Multipliers. Since the obtained dynamic equations are expressed in terms of independent generalized coordinates which are selected according to active joint variables of the arm, the equations could be best suitable for control law design and implementation. The simulation of the forward and inverse kinematics and dynamics of the arm demonstrates the motion behavior of the robot system.